Transient Budd–Chiari syndrome secondary to blunt traumatic bile fistula: A case report - Ma, Qimin; Cao, Kai; Luo, Pengfei; Liu, Xiaobin; Shen, Tuo; Wang, Yusong; Zhu, Feng (Frontiers in Surgery, 2022)
Budd-Chiari Syndrome is rarely caused by trauma. We reported a case of transient and secondary BCS post polytrauma resulted from massive perihepatic and abdominal fluid and compressed liver causing to stenosis of the inferior vena cava and hepatic veins. This was a special BCS case that related to trauma but not directly caused by trauma. With conservative management and active surgical procedures, the patient recovered well.